THE IMPLEMENTATION OF THE ADAPTIVE, ANTICIPATIVE, AND TRANSFORMATIVE SCHOOL BASED MANAGEMENT TO CREATE THE BEST SCHOOL - Millah, Dliyaul (VISION, 2014)
ABSTRACT School is one of the three main of education which is demanded to be able to create the best output. To create school to be the best, it needs the suitable operational of school management with the desirable principle and characteristic of special quality. For that reason, the headmaster is demanded to function the management that could optimize all school resources autonomously, accountable, and transparent. Decentralization of education offers new paradigm for the leader to be more autonomous and fostering entire school resource to be the best school. One of them is the change of education management where the schools are demanded to do the change of school management. To change central-based management or local-based management into school-based management is a long process that involves all related components. This change needs adjustments in the structure, culture and figure system through new demands on school-based management. School-based management is not âace in the holeâ that will deliver expectation on school reformation if it is implemented without innovative, creative, anticipative, and transformative leadership principles. Â  Key words: School-Based Management, The Best School, Adaptive, Anticipative, and Transformative Education.